Yale-NUS College as embassy and students as ambassadors: International student attraction and engagement strategies - Wong, Engie (Journal of International Students, 2026)
As Yale-NUS College came to its close in 2025, it represents a unique case study for examining the factors that attracted students from all over the world to Yale-NUS. Drawing upon extant literature on internationalization-at-home and international student mobilities, as well as mixed-methods interviews with key faculty and staff and a survey of students and alumni, this paper identifies an “ambassadorial spirit” in students whereby they strongly identify with and act as representatives of the College in order to improve brand reputation in Singapore and abroad. This ambassadorial spirit is formed through the selection of particular traits in the admissions process, the common experiences that bond students, and students’ interaction with the institution of Yale-NUS College. Altogether, this case study aims to distill the Yale-NUS experience into lessons for higher education institutions aiming to generate strong community identity and sense of belonging.